The Implications of COVID-19 Pandemic on Indoor Environments: Balancing Environmental Considerations and Wellbeing in Higher Educational Facilities - Shoukry, Farah (AUC Knowledge Fountain, 2024)
In this dissertation, the evolving problems concerning Indoor Air Quality (IAQ), and Indoor Environmental Quality (IEQ) in learning environments are examined. The topic is inspired by the COVID-19 pandemic and aspires to document the lessons learned via a vast set of investigations for enhanced IAQ management and control. Specifically, within educational buildings, the challenge remains to better inform the design and management of educational facilities to foster healthier and more sustainable learning environments. There are emerging research topics related to IAQ post the COVID-19 – including but not limited to: architectural design considerations of university classrooms, increase in carbon footprint of buildings, thermal discomfort in learning spaces, energy (in)efficiencies as a result of dependence on mechanical ventilation systems, as well as ample room for innovating tools to better manage IAQ in large scale facilities. This prompts us to identify the significance of such research topics, analyse their impacts, and start on the research journey to better understand them. The manuscript-based dissertation adopts a multifaceted approach to examine the implications of the COVID-19 pandemic on IAQ in higher educational buildings. Each chapter relied on its own set of qualitative and/or quantitative methods – including focus groups, surveys, energy simulation, field measurements and statistical analysis - to generate actionable recommendations for stakeholders involved in the design, operation, and management of educational facilities. The research yields several key interesting findings that shed light on the complex interplay between IAQ, environmental sustainability, and occupant well-being in educational settings. With no particular order, such findings include: (1)There is perceived difficulty in benchmarking carbon footprint reporting across regional university campuses to accurately reflect campuses' scale, population, geography, and nature of operations, which questions the type of metrics used for benchmarking. (2) Universities represent a potential strong key-player in accelerating the carbon footprint reporting culture on a city scale. (3) By implementing low-carbon strategies, such as improving fan efficiencies, and giving occupants control over the thermostat; thermal comfort can be greatly improved in learning classrooms. (4) There are changing needs for both students and educators on what to consider for the design of a university classroom which was inspired by the COVID-19 experience. Such identified needs are due to evolving pedagogical needs of the learning process, necessitating the incorporation of collaborative learning spaces, flexible seating arrangements, personalized control of the indoor environment, as well as areas for individual study There is ample opportunity for architects to design healthy learning spaces while checking-off multiple considerations: architectural components, educational requirements, technological channels, human aspects prerequisites, as well as contextual factors. (5) There are significant correlations observed between IAQ parameters, including carbon dioxide (CO2) levels, total volatile organic compounds (tVOC), occupancy rates, and particulate matter (PM) concentrations. These findings underscore the interconnected nature of indoor environmental factors and highlight the importance of holistic IAQ management strategies. (6) A predictive equation – model - could be used to better estimate the mechanical ventilation energy within university classrooms based on classroom configuration, occupancy and window location. This would enable facility managers in the future to better to translate such estimations into fiscal values and save on operational costs while maintaining acceptable IAQ levels within classrooms. Finally, (7) it is viable to balance IAQ environmental considerations and well-being of occupants in the built environment via specialized indoor monitoring systems and communication tools. Among the practical tools to achieve this balance is to utilize an enhanced IAQ dashboard for monitoring different spaces within an educational facility, and appropriating a Classroom Index to compare IAQ, IEQ and Thermal Comfort conditions in selected learning spaces. Based on such research findings, several key actionable recommendations emerge addressing environmental researchers, architects, designers, policymakers, IAQ industry experts as well as facility managers. The key message is: by adopting a holistic approach to IAQ management and embracing sustainable practices, educational institutions can create healthier more resilient learning environments that support academic success and environmental stewardship.